2012
DOI: 10.1021/ol302557a
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Oxa- and Aza-Angular Triquinanes Using Tandem Radical Cyclization to Vinylogous Carbonates and Carbamates

Abstract: Tandem radical cyclization to vinylogous carbonates and carbamates is developed for a new, highly stereoselective synthesis of heterocyclic angular triquinanes. The strategy is also useful to gain access to oxa- and azatriquinanes, which incorporate the spiroindoline moiety. The method is further extended to the synthesis of lactone-bearing as well as uracil-fused angular triquinanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…When 4cyanobenzal diacetate 1 g was subjected to the present reaction under the conditions shown as entry 1 in Table 3, the corresponding mandel acetate 2 g was obtained in 54 % yield. However, over reduction product, 4-cynophenylacetic acid (7), was also produced even by 7.5 mA/cm 2 of lower current density with 2 F/mol of less electricity, in other word under milder electroreductive conditions, than those shown in Table 2. After our several efforts, it was found that, instead of magnesium, zinc is effective as an anode to suppress the formation of 7.…”
Section: Efficient Synthesis Of Mandel Acetates By Electrochemical Camentioning
confidence: 90%
See 1 more Smart Citation
“…When 4cyanobenzal diacetate 1 g was subjected to the present reaction under the conditions shown as entry 1 in Table 3, the corresponding mandel acetate 2 g was obtained in 54 % yield. However, over reduction product, 4-cynophenylacetic acid (7), was also produced even by 7.5 mA/cm 2 of lower current density with 2 F/mol of less electricity, in other word under milder electroreductive conditions, than those shown in Table 2. After our several efforts, it was found that, instead of magnesium, zinc is effective as an anode to suppress the formation of 7.…”
Section: Efficient Synthesis Of Mandel Acetates By Electrochemical Camentioning
confidence: 90%
“…Mandelic acid, 2-hydroxy-2-phenylacetic acid, and its derivatives are useful and important as synthetic intermediates [1] and biologically-active compounds. [2] Mandelic acid has been prepared from benzaldehyde by using HCN/cyanide ion, [3][4][5][6][7] chloroform/bromoform [2a, [8][9][10] or ethynylmagnesium bromide [2b] as a carbon source of the carboxyl group although these reagents are unfavorable from the viewpoint of green chemistry and functional group tolerance. Carbon dioxide, on the other hand, would also be a useful and favorable carbon source for synthesis of mandelic acid since it is a non-toxic, abundant, economical, and environmentally benign C1 chemical reagent.…”
Section: Efficient Synthesis Of Mandel Acetates By Electrochemical Camentioning
confidence: 99%
“…Radical translocation by 1,5‐hydrogen abstraction and the following cyclization are also characteristic reactions of vinyl radicals . One representative and frequently used method to generate such vinyl radicals involves reaction of alkynes with Bu 3 SnH/AIBN (azobisisobutyronitrile), and many successful applications of the thus‐generated vinyl radicals in cyclizations affording carbo‐ and heterocycles have been reported . Regioselectivity in the generation of vinyl radicals from internal alkynes has been, however, sometimes troublesome and problematic .…”
Section: Screening Of Reaction Conditionsmentioning
confidence: 99%
“…[3][4][5][6][7] One representative and frequently used method to generate such vinyl radicals involves reaction of alkynes with Bu 3 SnH/AIBN (azobisisobutyronitrile), [8] and many successful applications of the thus-generated vinyl radicals in cyclizationsa ffording carbo-andh eterocyclesh ave been reported. [8][9][10][11][12][13][14][15][16] Regioselectivity in the generation of vinyl radicals from internal alkynes has been, however,s ometimes troublesomea nd problematic. [17] On the other hand, vinyl bromide and iodide are good and straightforward precursors for vinyl radicals.…”
mentioning
confidence: 99%
“…The gem-difluoromethylketobicyclic compound 6 a was obtained after passing the crude reaction mixture through silica gel, eluting with CH 2 Cl 2 . [10] Alternatively, 7 a resulted from 4 aB upon hydrogen atom abstraction from Bu 3 SnH and subsequent reductive cleavage of the phenylsulfanyl group initiated by a tributylstannyl radical. At a high concentration of 4 a in toluene (0.02 m) and excess Bu 3 SnH (1.20 or 1.75 equiv), the intermediate 4 aE can further react with the tributylstannyl radical, thus leading to defluorinated products 8 a and 9 a, after treatment with silica gel in CH 2 Cl 2 .…”
Section: Entrymentioning
confidence: 99%